2020
DOI: 10.1371/journal.pcbi.1007147
|View full text |Cite
|
Sign up to set email alerts
|

Model-based analysis of response and resistance factors of cetuximab treatment in gastric cancer cell lines

Abstract: Targeted cancer therapies are powerful alternatives to chemotherapies or can be used complementary to these. Yet, the response to targeted treatments depends on a variety of factors, including mutations and expression levels, and therefore their outcome is difficult to predict. Here, we develop a mechanistic model of gastric cancer to study response and resistance factors for cetuximab treatment. The model captures the EGFR, ERK and AKT signaling pathways in two gastric cancer cell lines with different mutatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“… 23 Amplifications, mutations, or overexpression of MET, HER2, or ERBB3 have been found to help the downstream signaling of EGFR remain activated, thereby reducing the tumor sensitivity to EGFR-targeted therapy. 24 - 26 Several drugs targeting these amplifications or overexpression initially re-sensitize tumors to cetuximab, but generally fail due to drug resistance. 25 - 27 Therefore, it is clinically relevant to explore other potential strategies to improve the efficacy of cetuximab on gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Amplifications, mutations, or overexpression of MET, HER2, or ERBB3 have been found to help the downstream signaling of EGFR remain activated, thereby reducing the tumor sensitivity to EGFR-targeted therapy. 24 - 26 Several drugs targeting these amplifications or overexpression initially re-sensitize tumors to cetuximab, but generally fail due to drug resistance. 25 - 27 Therefore, it is clinically relevant to explore other potential strategies to improve the efficacy of cetuximab on gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is often challenging and even infeasible for models with large datasets, since the number of observation parameters can easily exceed the number of model parameters (see e.g. [26, 27]).…”
Section: Resultsmentioning
confidence: 99%
“…As the marginalization-based approach appeared beneficial for challenging problems, we assessed in a next step whether it enables Bayesian inference for problems for which standard approaches did not provide reproducible results in a reasonable time-frame. Specifically, we considered an ODE model for signal transduction in gastric cancer cells (cell line MKN1) that was developed to unravel response and resistance markers [27]. This model possesses in total 57 unknown parameters, of which 26 are model parameters and 31 are observation parameters (Table 1, M4).…”
Section: Marginalization-based Approach Enables Bayesian Inference Fo...mentioning
confidence: 99%
“…This further inhibits cancer cell proliferation and induces cancer cell apoptosis. [16] As early as >10 years ago, studies reported that tyrosine kinase inhibitors (TKIs) gefitinib and erlotinib were not effective in treating GC, while monoclonal antibodies (mainly cetuximab) were found to be effective in some published experimental studies. [17,18] A randomized, multicenter phase II clinical study (NCT00477711) in China explored the efficacy of cetuximab combined with cisplatin and capecitabine (C + XP) in treating advanced gastric or esophagogastric junction adenocarcinoma.…”
Section: Anti-egfr Antibodiesmentioning
confidence: 99%
“…Cetuximab can bind to EGFR on the surface of tumor cells, thus inhibiting the interaction with its ligands and blocking the intracellular signal transduction pathway. This further inhibits cancer cell proliferation and induces cancer cell apoptosis [16] …”
Section: Epidermal Growth Factor Receptor (Egfr) Family-targeted Drugsmentioning
confidence: 99%